Knowledge and Attitude toward Smoke-Free Legislation and Second-Hand Smoking Exposure among Workers in Indoor Bars, Beer Parlors and Discotheques in Osun State of Nigeria - Olanrewaju Olusola Onigbogi; Oluwakemi Odukoya; Modupe Onigbogi; Oluwakemi Sekoni (Kerman University of Medical Sciences, 2015)
Background One of the requirements of the Osun State smoke-free legislation is to ensure smoke-free enclosed and partially enclosed workplaces. This survey was conducted to assess the knowledge and attitude of workers in indoor bars, beer parlors and discotheques to smoke-free legislation in general and the Osun State smoke-free law in particular. Methods A convenience sampling of 36 hospitality centers was conducted. Interviewer-administered questionnaires were used to elicit responses about the objectives from non-smoking workers. The questionnaires had sections on knowledge of the Osun State smoke-free law, attitude toward the law and smoke-free legislation in general and exposure to second-hand tobacco smoke by the workers. Questions were also asked about the secondhand tobacco smoking status of these workers. The data were analyzed using SPSS version 15.0. Results We had 154 participants recruited into the study. There were 75 males (48.0%) and 79 females (52.0%). On the overall, respondents had a good knowledge of the effects of second-hand smoke on health (70.2%) with 75.0% of them being aware of the general smoke-free law and 67.3% being aware of the Osun State smoke-free law although none of them had ever seen a copy of the law. A high proportion (60.0%) was in support of the Osun smoke-free law although all of them think that the implementation of the law could reduce patronage and jeopardize their income. Attitude toward second-hand smoking was generally positive with 72.0% of them having no tolerance for second-hand tobacco smoke in their homes. Most participants (95.5%) had been exposed to tobacco smoke in the workplace within the past week. Conclusion Despite the high level of awareness of the respondents about the dangers of second hand smoke and their positive attitude to smoke-free laws, nearly all were constantly being exposed to second hand smoke at work. This calls for policy level interventions to improve the implementation of the smoke-free law.